Effect of semen sojae germinatum on experimental osteoarthritis in the rabbit knee - Bingshu He; Jun Wang (Bangladesh Pharmacological Society, 2013)
As a complementary therapeutic approach, soy ingredients, such as soy protein and soybean unsaponifiables, recently attract more attention for relieving symptoms of osteoarthritis (OA). Semen sojae germinatum (SSG) processed from bean-sprout coming from germinating Glycine maxL. Merr. is a traditional Chinese herbal medicine treating knee OA. We evaluated the effect of SSG as feed on the development of anterior cruciate ligament transaction (ACLT) -induced knee OA in rabbits. The results showed that SSG reduced the severity of cartilage degeneration in macroscopic grading scale, and delayed the degradation of the cartilage matrix. The contents of prostaglandin E2 (PGE2), nitric oxide (NO), tumor necrosis factor (TNF)-α, interleukin-6(IL-6) and IL-1β in synovial fluid, mRNA and protein expressions of matrix metalloproteinases (MMP)-3, MMP-13 in cartilage were effectively decreased in SSG group. These results demonstrate that SSG had a protective effect against the development of knee OA.